Rezension von: Meier, Robert, 1628 Wertheim - Müller, Peter (Zeitschrift für Württembergische Landesgeschichte, 2016)
Robert Meier, Wertheim 1628 – Eine Stadt in Krieg und Hexenverfolgung, Dettelbach: Verlag J. H. Röll GmbH 2015. 120 S. ISBN 978-3-89754-464-2. € 14,95